2017
DOI: 10.1007/s13205-016-0591-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of Lactobacillus isolates of curd and human milk origin against food-borne and human pathogens

Abstract: This study was undertaken to assess the antibacterial efficacy of lactobacilli isolated from curd and human milk samples. Identities of thirty-one different lactobacilli (20 from curd and 11 from human milk) were confirmed by genus-specific PCR and 16S rRNA-based sequencing. These strains belonged to five species, Lactobacillus casei, L. delbrueckii, L. fermentum, L. plantarum, and L. pentosus. Antibacterial activities of cell-free supernatants (CFSs) of all the Lactobacillus isolates were estimated through st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 44 publications
(53 reference statements)
2
38
1
4
Order By: Relevance
“…However, it is also important that the resistance should be inherent and non-transferrable. Natural antimicrobial properties of LABs may further pose a synergistic effect to antibiotic therapy in eliminating pathogenic strains (Sharma et al 2017). Further, synergistic application of different antibiotics groups may display strong activity against resistant strains and may prevent build-up of strong resistance in strains currently showing intermediate susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important that the resistance should be inherent and non-transferrable. Natural antimicrobial properties of LABs may further pose a synergistic effect to antibiotic therapy in eliminating pathogenic strains (Sharma et al 2017). Further, synergistic application of different antibiotics groups may display strong activity against resistant strains and may prevent build-up of strong resistance in strains currently showing intermediate susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus spp. produce a wide variety of antimicrobial compounds such as organic acids (lactic acid, acetic acid, and propionic acid), peroxides, bacteriocins, and antimicrobial peptides (De Vuyst & Leroy, ; Jamuna & Jeevaratnam, ; Sharma et al, ). Lactobacilli may produce acids through the heterofermentative pathway, which promotes the antibacterial effect probably via physiological and morphological changes in the bacterial cytoplasmic membrane, resulting in the leakage of the cytoplasmic content (Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, such resistance should be intrinsic and non-transferable; as intrinsic resistance and resistance due to mutation of chromosomal genes present a low risk of horizontal dissemination. Further, antimicrobial potential of LAB further enhances the efficacy of antimicrobial drug therapy, as it also helps in eradicating the pathogenic microorganism (Sharma et al, 2017b). In the current study, we have observed a wide range of resistance among goat Lactobacillus isolates; therefore further studies are needed to understand the resistance mechanisms on molecular basis.…”
Section: Resultsmentioning
confidence: 99%
“…from raw goat (Beetal) milk obtained from dairy farm of Guru Angad Dev Veterinary and Animal Sciences University (GADVASU) Ludhiana, Punjab, India. Milk samples were processed and lactobacilli were isolated and identified as discussed previously (Panwar et al, 2016;Sharma et al, 2017a and2017b …”
Section: Bacterial Strainsmentioning
confidence: 99%